2006
DOI: 10.1038/nature04488
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual reproduction selects for robustness and negative epistasis in artificial gene networks

Abstract: The mutational deterministic hypothesis for the origin and maintenance of sexual reproduction posits that sex enhances the ability of natural selection to purge deleterious mutations after recombination brings them together into single genomes. This explanation requires negative epistasis, a type of genetic interaction where mutations are more harmful in combination than expected from their separate effects. The conceptual appeal of the mutational deterministic hypothesis has been offset by our inability to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
294
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(318 citation statements)
references
References 26 publications
17
294
5
Order By: Relevance
“…Our results appear to differ from those of Azevedo et al (2006), although these authors did not use a modifier gene to alter epistasis. They found that with recombination there should generally be selection towards (negative) synergistic epistasis.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our results appear to differ from those of Azevedo et al (2006), although these authors did not use a modifier gene to alter epistasis. They found that with recombination there should generally be selection towards (negative) synergistic epistasis.…”
Section: Discussioncontrasting
confidence: 56%
“…Thus how the shape of this function evolves is also important. An approximate numerical treatment by Azevedo et al (2006) concluded that when deleterious mutations can recombine there should be selection towards negative (synergistic) epistasis, but without recombination, positive epistasis should evolve. Understanding how epistasis evolves has broader implications, as epistatic interactions are "central to the evolution of genetic recombination" (Michalakis and Roze 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This dependence, known as epistasis, is important to many areas of developmental and evolutionary biology, including speciation [1][2][3][4], the maintenance of sex [5,6], adaptation [7][8][9], the evolution of ploidy [10] and evolutionary contingency [11 -14]. As the technology to identify and manipulate specific mutations becomes increasingly available, the influence of epistasis can be examined directly.…”
Section: Introductionmentioning
confidence: 99%
“…where f b is a standard sigmoidal filter function (see Methods; see also electronic supplementary material, figure S4a) [8]. As with the direct effects of loci, the epistatic effects were allowed to mutate and vary within the population, and evolve.…”
Section: Results and Discussion (A) Genetic Architectures Predicted Bmentioning
confidence: 99%
“…The resulting genetic architecture of a trait [1] influences its variational properties [2][3][4][5], and therefore affects a population's capacity to adapt to new environmental conditions [1,6,7]. Over longer time scales, genetic architectures of traits have important consequences for the evolution of recombination [8] and of sex [9], and even reproductive isolation and speciation [10].…”
Section: Introductionmentioning
confidence: 99%